2020
DOI: 10.18231/j.tjp.2020.033
|View full text |Cite
|
Sign up to set email alerts
|

Study of referrals to department of psychiatry in tertiary care general hospital setting

Abstract: Background: Study of referral pattern to psychiatry helps us to understand the type of patients and the rate of referral from individual departments. It also helps us to understand the need for consultation liaison services (CLP) thereby strengthening the General Hospital Psychiatric Units (GHPU) Aim: To study the referral pattern to psychiatry in a tertiary care teaching hospital. Materials and Methods: All referrals to the department of psychiatry for a period of two months were included in the study. Sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…A study conducted in Telangana by Srilakshmi Pingali et al (2020) showed similar results, but most referrals were of age 25-35 years, unemployed, and belonging to low SES. 3 In a study conducted by Iniyan Selvamani et al (2022) in 310 referral patients, the mean age of the sample was 40.6 years with an SD of 16.3, and the majority (64.19%) were males. 8 In our study, the majority of the cases referred were inpatients (61%), and most of them were from the medical specialties (85%), [General medicine -55, Neurology-21] followed by surgical branches (15%).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…A study conducted in Telangana by Srilakshmi Pingali et al (2020) showed similar results, but most referrals were of age 25-35 years, unemployed, and belonging to low SES. 3 In a study conducted by Iniyan Selvamani et al (2022) in 310 referral patients, the mean age of the sample was 40.6 years with an SD of 16.3, and the majority (64.19%) were males. 8 In our study, the majority of the cases referred were inpatients (61%), and most of them were from the medical specialties (85%), [General medicine -55, Neurology-21] followed by surgical branches (15%).…”
Section: Discussionmentioning
confidence: 95%
“…"Liaison" refers to the linking up of groups for effective collaboration. 2 In a study conducted in Telangana by Srilakshmi Pingali et al (2020), most of the referrals were in the age group of 25-35 years, the majority were males (65%) and Hindu by religion (85%) and residing in rural areas (53.6%). Most of the patients were illiterate (37.9%), unemployed (30%), and belonged to low socioeconomic status (95%).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations